Troglocaris (Xiphocaridinella) kumistavi sp. nov., a new species of stygobiotic atyid shrimp (Crustacea: Decapoda: Atyidae) from Kumistavi Cave, Imereti, Western Georgia, Caucasus - Marin, Ivan (Zootaxa, 2017)
A new species of stygobiotic atyid shrimp genus Troglocaris (Xiphocaridinella) Dormitzer, 1853 from underground stream and lakes of Kumistavi (Prometheus) Cave, Tskaltubo, Imereti region, Western Georgia is described based on morphology and DNA analysis. Troglocaris (Xiphocaridinella) kumistavi sp. nov. clearly differs from all Caucasian congeners by (1) long slender dorsally and ventrally armed rostrum with sting-like tip turned upward, (2) very slender fingers of pereiopod II both in males and females and (3) distally expanded telson with 5–7 pairs of distal spines. These features are rather unique within the known Caucasian Troglocaris (Xiphocaridinella) and show some morphological similarities with Dinaric species of the genus. Neotype of Troglocaris (Xiphocaridinella) kutaissiana (Sadowsky, 1930) is also designated based on the material from Tskaltsitela Cave, Kutaisi, Georgia.